68-4x=5x+17

Simple and best practice solution for 68-4x=5x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 68-4x=5x+17 equation:


Simplifying
68 + -4x = 5x + 17

Reorder the terms:
68 + -4x = 17 + 5x

Solving
68 + -4x = 17 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
68 + -4x + -5x = 17 + 5x + -5x

Combine like terms: -4x + -5x = -9x
68 + -9x = 17 + 5x + -5x

Combine like terms: 5x + -5x = 0
68 + -9x = 17 + 0
68 + -9x = 17

Add '-68' to each side of the equation.
68 + -68 + -9x = 17 + -68

Combine like terms: 68 + -68 = 0
0 + -9x = 17 + -68
-9x = 17 + -68

Combine like terms: 17 + -68 = -51
-9x = -51

Divide each side by '-9'.
x = 5.666666667

Simplifying
x = 5.666666667

See similar equations:

| -3y+2=-13 | | 59a+4=36 | | 3x+1=(x-9) | | (2x+3)(2x+5)(x-1)(x-2)=30 | | -10t-2=0 | | -10t^2-2t=0 | | 4x-(3x+7)=-1 | | 2x+3x-2=98 | | 5(4x-6)-8=6x-24 | | 2x^2+9*x-7=0 | | x-22=4 | | x+5+133+x= | | x^3+4x^2+5x+2=0 | | 3(5a-2)-2a+10= | | 3(n-1.8)=2n+1 | | 6(x-1)-2(2-x)=8-(2-6x) | | x^4+4x^3+5x^2+2x=0 | | q*(5-q)= | | 3y=-28-x | | 2(1+x)-1=3(2x+1)+2 | | z-48=-32 | | (5-q)-5q= | | 8x-1/5-1=(50-2x/9)+(3x+3/4) | | 16x+7x+15=0 | | 5-q= | | 10n=4 | | 5x-4=14x-13 | | 3x+26=10x-41 | | 20*(4x+1)-24(3x+1)=15*60-60*(25-x) | | 15x-176=6x-14 | | 24*(3x-1)-20*(5x+1)=120*(x+1)-3*120 | | 6y+(8)(7)-4=42 |

Equations solver categories